Pelatihan Manajemen Website Rumah Sakit Khusus Gigi dan Mulut Provinsi Sumatera Selatan - Nur Rachmat; Johannes Petrus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The Special Dental and Oral Hospital of South Sumatra Province has an official WordPress-based website (https://rsgigimulut.co.id/) that functions as a medium for information dissemination, communication, and public services to the community. This website is expected to provide accurate, up-to-date, and easily accessible information for users. However, in practice, the website management staff still face challenges and limitations in independently managing and updating the content, resulting in the suboptimal utilization of the website’s potential. This community service activity aims to provide website management training for the staff by utilizing the WordPress Content Management Sistem (CMS) so that they are able to manage the website effectively and sustainably. The training was conducted on August 11, 2025, in the third-floor meeting room of the Special Dental and Oral Hospital of South Sumatra Province, involving two website management staff members. The implementation methods included lectures, demonstrations, and hands-on practice covering the introduction to the WordPress interface, page layout customization, the addition of new posts and pages, menu creation and management, as well as tips on content management and website maintenance. The results of the training indicate an improvement in participants’ understanding and skills in independently managing the website, which has a positive impact on enhancing the quality of public information presentation and strengthening the hospital’s digital services.